Ensinar ciências no ensino fundamental II: possibilidades e desafios na percepção de professores iniciantes. - Lazarim, Carol Alice Petroski (2023)
The start of teaching is a time full of lessons that extend over the professional career of teachers, so it is common to have a higher number of doubts in relation to the school dynamics and the pedagogical work. Considering this topic, our main goal was to understand the challenges that permeate the beginning of teachers’ careers who teach the subject of Science in Elementary School II from the State System of Education of Cascavel-PR. With epistemological focus founded on phenomenological and hermeneutical assumptions, we seek to understand the participants’ perceptions regarding the early professional training and practice, especially in regards to the challenges encountered and achievements made. With that, our aim is to answer the following research question: What is shown in beginner teachers’ discourses about the challenges of teaching Science in the final years of Elementary School? Therefore, we sought with the particular goals: to identify through bibliographic research, what is revealed about the investigated topic; to interpret the interviews and relate them to the discouses found in studies already realized; to analyze the profile of the research’s interlocutors, as well as their perceptions about the struggles present in the beginning of the profession; and to raise reflections that collaborate for an effective articulation between teaching training and practice, indicating possibilities of improvement. This qualitative study is exploratory, in which we used a bibliographic search and field research as technical procedures. The data constituted by semi-structured interviews with beginner teachers in practice at public schools, were explored by means of Discourse Textual Analysis and took to the rise of two final analysis categories, which are: 1. Continuous training and collaborative work: pillars of teaching and 2. In overcoming insecurities, lies the ability to reinvent itself. The results reveal that there are different challenges faced in the first years of practice, such as: difficulties of entering the system; professional instability; impacts before the school reality; struggles with bureaucratic attributions; lack of infrastructure; insufficiency of didactic resources; excessive work demands; brief time available for working on planned content; absence of interest from many students; increase of discrepancy due to the pandemic; and having to deal with adverse issues that reflect in classrooms. Even with a short time in practice, teachers demonstrate abilities to teach the Science subject contents with what is available at the schools, expressing dedication so that the students’ learning can be more active, autonomous and significant. Lastly, we signal that teaching is perfected over time, it is a continuous process of building and rebuilding knowledge that consolidates daily in different practices held in class.